Scheelite ore deposit associated with lamprophyres and biotitite in San Martín District, San Luis Province - Montenegro, T. (2009)
Towards the northeast of the Sierra de San Luis several wolfram ore deposits occur. In San Martín district they are divided into three groups: Los Avestruces, La Esperanza and Cerrito Blanco. The geology of this area is formed of the Conlara metamorphic complex composed of schists (with a strike of 300° north), granitoids and pegmatites. In the same area subsaturated chalco-alkaline lamprophyres also appear as subvertical bodies with NW-NE strikes. Toward the boundaries of these rocks, the amount of biotite rises gradually from 80 to 90% developing a biotitite rock due to metasomatic processes and the superimposed deformation. This biotitite is rich in K, Rb and W among other elements. The scheelite mineralization (with quartz, biotite and tourmaline as non ore minerals) occurs in veins that are usually hosted between the lamprophyres and the wall rocks. Scheelite also appears between the schist planes of the biotitite rocks as well as disseminated crystals in quartz aggregates. This mineralization took place from fluids with XH2O: 0.87/0.82 - XCO2: 0.11/0.16 - XNaCl: 0.015/0.013 - (CH4) meanwhile the scheelite, according to the fluid inclusions studies, precipitated from unmixing processes below 320°C and 2.3 kb. Achaliana orogeny and the intrusion of Las Chacras-Piedras Coloradas batholiths (Devonian-Carboniferous) were the responsible for the slight rise of the fluids from the basement, the generation of fault structures through which they rose, the metasomatism and the mineralization.